Malay Ethnomathematics: Analysis of Mathematics Learning Problem Solving based on Riau Malay Culture - Darto, Darto; Mudasir, Mudasir; Thahir, Musa; Muhtady, Dedi (Instructional Development Journal, 2025)
The problem in learning mathematics today is that students' mathematics learning outcomes are still low, this is because students are less able to understand mathematical concepts and problem solving. The socio-cultural environment in mathematics can increase students' social interaction in learning mathematics. The process of learning mathematics should be associated with the socio-cultural environment of students. This study aims to analyze problem solving mathematics learning based on Riau Malay culture on the subject of two-dimensional figures or flat shapes. This type of research is a descriptive qualitative research. This type of research was conducted at Junior High School 1 Bunga Raya, Siak Regency for the academic year 2021/2022. The results of this research are the Analysis of Mathematics Learning “Problem Solving” based on Riau Malay Culture on the subject of flat shapes at high, medium and low levels. The percentage at each level is high 83.8%, medium 12.9% and low 3.3%